Implementasi Dashboard Data Untuk Analisis Penjualan Properti Menggunakan Business Intelligence pada PT Winka Karisma Gemilang QQ Edwin Bright Properti - Alfan Hidayat; Farizi Ilham; Naira Aqeela Fahmi; Nazwa Aulia Sihan (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
PT Winka Karisma Gemilang is a company engaged in property sales and marketing that still faces challenges in managing sales data. The use of Microsoft Excel as the primary data management tool results in unintegrated data, difficulties in conducting real-time analysis, and potential input errors. These issues lead to delays in information delivery and less effective managerial decision-making processes. This study aims to implement a Business Intelligence-based dashboard to support property sales analysis in a faster, more accurate, and interactive manner. The system was developed using the Waterfall method, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. Research data were collected through observation, interviews, and literature studies. The results indicate that the developed dashboard is capable of presenting sales information through data visualization, Key Performance Indicators (KPI), sales trend analysis, and real-time agent performance monitoring. The implemented system improves data processing efficiency, facilitates sales monitoring activities, and supports more effective decision-making within the company.